Characterization of Cronobacter spp. isolated from food products in Poland and comparative genomic analysis of Cronobacter sakazakii isolate MK_10 and a clinical strain associated with a fatal neonatal infection - Korsak, Dorota; Szuplewska, Magdalena; Kozłowska, Paulina; Krakowski, Kamil; Chmielowska, Cora; Wawrzyniak, Paweł; Maćkiw, Elżbieta; Bartosik, Dariusz (Frontiers in Microbiology, 2025)
Cronobacter spp. are ubiquitous environmental bacteria associated with infections affecting all age groups, with infants and elderly individuals particularly at risk. We investigated the prevalence of Cronobacter spp. in 251 food samples collected in Poland, including raw milk, powdered milk, infant formula, dried herbs and spices, dried teas, and raw vegetables. Cronobacter strains were isolated from 26 samples (10.4%) and classified into five species: C. sakazakii, C. muytjensii, C. turicensis, C. malonaticus and C. dublinensis. The isolates were grouped based on sequence variation of the fusA and rpoB genes, and further differentiated according to their biochemical profiles. The complete nucleotide sequence of C. sakazakii MK_10, a plasmid-rich strain isolated from dried oregano and representing the most prevalent species in the collected strain pool, was obtained. Comparative genomic analysis of MK_10, the first fully sequenced foodborne C. sakazakii strain in Poland, with a clinical strain from a fatal neonatal case revealed the presence of a conserved set of genes associated with pathogenic properties. MK_10 carries three extrachromosomal replicons, including two IncFIB plasmids – pCS-MK10_P1 (114 kb), representing the pESA3 family of virulence plasmids, and pCS-MK10_P2 (45.9 kb) carrying a copper homeostasis and silver resistance island (CHASRI). Comparative analyses revealed that the structure of the MK_10 chromosome has been shaped by multiple insertion and deletion events, associated mainly with prophages (e.g., a novel intact prophage related to Cronobacter phage ENT47670) and other integrative elements. The MK_10 genome contains only two transposable elements: an isoform of insertion sequence ISEhe2 (IS3 family) and a non-autonomous Tn3-family transposon of unique structure – both located within two functional integrative elements (IE), designated IECsakMK101 (32.3 kb) and IECsakMK102 (32.4 kb). The identified mobile genetic elements, plasmids, and IEs, harbor genes of adaptive value, which potentially contribute to the strain’s environmental fitness and pathogenic potential.